Direct and Indirect Effects of Penguin Feces on Microbiomes in Antarctic Ornithogenic Soils - Guo, Yudong; Wang, Nengfei; Li, Gaoyang; Rosas, Gabriela; Zang, Jiaye; Ma, Yue; Liu, Jie; Han, Wenbing; Cao, Huansheng (Frontiers in Microbiology, 2018)
Expansion of penguin activity in maritime Antarctica, under ice thaw, increases the chances of penguin feces affecting ornithogenic soil microbiomes. The detail of such effects was only recently studied so far (Santamans et al, 2017). By comparing soil geochemistry and microbiome composition in (one site) and outside (three sites) of the rookery, we found significant effects of penguin feces on both. First, penguin feces change soil geochemistry, causing increased moisture content of ornithogenic soils and nutrients C, N, P, and Si in the rookery compared to non-rookery sites, but not pH. Second, penguin feces directly affect microbiome composition in the rookery, not those outside. Specifically, we found 4364 OTUs in 404 genera in six main phyla: Proteobacteria, Actinobacteria, Gemmatimonadetes, Acidobacteria, Chloroflexi, and Bacteroidetes. Although the diversity is similar among the four sites, the composition is different. For example, penguin rookery has a lower abundance of Acidobacteria, Chloroflexi, and Nitrospirae but a higher abundance of Bacteroidetes, Firmicutes, and Thermomicrobia. Strikingly, the family Clostridiaceae of Firmicutes is most abundant in the rookery than non-rookery sites with two most abundant genera, Tissierella and Proteiniclasticum. Redundancy analysis showed all measured geochemical factors are significant in structuring microbiomes, with moisture content showing the highest correlation. We further extracted 21 subnetworks of microbes which contain 4318 of the 4364 OTUs using network analysis and are closely correlated with all geochemical factors except pH. Our finding f penguin feces, directly and indirectly, affects soil microbiome suggests an important role of penguins in soil geochemistry and microbiome structure of maritime Antarctica.